Transculturalism as Conveyed in Kiran Desais The Inheritance of Loss - Selma Valeska Adriana; Ira Rasikawati (Journal of Language and Literature, 2018)
This study presents an analysis of cultural values and the idea of transculturalism as conveyed in The Inheritance of Loss, a novel written by Kiran Desai. The novel portrays the euphoria of globalization and the cultural issues faced by Indian immigrants in the West. Through her main characters Jemubhai, Biju, and Sai Desai implies her idea of transculturalism. The characters journey through the post-colonial era in different cultural settings offers insights into how the characters negotiate the differences between cultures and contexts. This study critically analyzed the characters attitudes from the hybridity theory perspective to unravel the authors voice about transculturalism. The three analysis stages performed were to determine key story elements associated to the transcultural theme, to classify the evidence supporting the theme emerged, and to interpret the findings using the new historicism approach and in view of the hybridity theory. In response to the two questions raised on what cultural values inferred from the characters view and what idea of transculturalism conveyed through the authors voice, this study found that the characters offered differing perspectives on cultural permeation and blending. The author suggested the consequences of resistance to cultural diversity.Keywords: transculturalism, hybridity, post-colonialism